Disc stability after condylar discopexy with open surgery technique. A case report. (International Journal of Medical and Surgical Sciences, 2019)
Of the temporomandibular joint (TMJ) pathologies, temporomandibular disorders (TMD) of disc displacement present several clinical signs and symptoms, the main ones being joint pain measured with the visual analogue scale (VAS) reporting on average VAS>6, and functional incapacity measured in mm of mouth opening, reporting on average